Expressive Speech Acts in Food Battle Content on YouTube Channels Tasyi Athasyia - Ayuning Jenia Ayunda Putri; Mangatur Sinaga; Tria Putri Mustika (Raja Zulkarnain Education Foundation, 2026)
This study aims to describe the forms and functions of expressive speech acts in food battle content on the YouTube channel of Tasyi Athasyia. This research was conducted in a virtual environment, namely the YouTube channel of Tasyi Athasyia. This study employed a descriptive qualitative research design aimed at describing the observed phenomenon as it is, without applying any special treatment to the variables under investigation. The research data consisted of verbal utterances containing expressions of feelings, attitudes, and evaluations conveyed by Tasyi Athasyia in food battle content. The research instrument in this study was the researcher as the main instrument (human instrument), supported by a data classification table. Data collection techniques were carried out through observation and note-taking techniques. The data analysis technique used the descriptive qualitative analysis model of Miles and Huberman, which includes data reduction, data display, and conclusion drawing. The results of the study showed that 227 expressive utterances were found from six videos analyzed. These utterances were classified into four forms of expressive speech acts, namely direct literal speech acts, direct non-literal speech acts, indirect literal speech acts, and indirect non-literal speech acts. In addition, nine functions of expressive speech acts were identified, namely expressing gratitude, congratulating, apologizing, expressing condolences, welcoming, praising, criticizing, complaining, and greeting. The findings indicate that expressive speech acts are used to convey emotions, evaluations, and to build communicative interaction with audiences in food battle content.